2020
DOI: 10.3390/ijerph17176414
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Single-Leg Landing Movement Capability Analysis According to the Type of Sport Practiced

Abstract: (1) Background: Understanding children’s motor patterns in landing is important not only for sport performance but also to prevent lower limb injury. The purpose of this study was to analyze children’s lower limb joint angles and impact force during single-leg landings (SLL) in different types of jumping sports using statistical parametric mapping (SPM). (2) Methods: Thirty children (53.33% girls, M = 10.16 years-old, standard deviation (SD) = 1.52) divided into three groups (gymnastics, volleyball and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In concrete, children between 3 and 4.5 years flexed less the knees and exhibited slower ankle dorsi-flexion during the braking phase, while smaller ankle dorsi-flexion and ankle range of motion was observed for the children between 4.5 and 6 years. It is suggested that a more efficient and mature landing performer will use multi-joint flexion of the leg and trunk to increase the duration of the post-landing period (corresponding to our braking phase) and then actively dissipate kinetic energy within a longer time period (McKay et al, 2005;Liebermann, 2008;Estevan et al, 2020). Our results are consistent with studies that proposed that less skilled children landing presented poor control of the ankle dorsiflexion (Hinrichs et al, 1985;Mckinley and Pedotti, 1992).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In concrete, children between 3 and 4.5 years flexed less the knees and exhibited slower ankle dorsi-flexion during the braking phase, while smaller ankle dorsi-flexion and ankle range of motion was observed for the children between 4.5 and 6 years. It is suggested that a more efficient and mature landing performer will use multi-joint flexion of the leg and trunk to increase the duration of the post-landing period (corresponding to our braking phase) and then actively dissipate kinetic energy within a longer time period (McKay et al, 2005;Liebermann, 2008;Estevan et al, 2020). Our results are consistent with studies that proposed that less skilled children landing presented poor control of the ankle dorsiflexion (Hinrichs et al, 1985;Mckinley and Pedotti, 1992).…”
Section: Discussionsupporting
confidence: 87%
“…Research focused on the development of landing mainly compared children around 9-10 years old and adults considering different types of landing. These types can be grouped on (1) drop-land tasks, which entails hanging from a bar or taking off from an elevated platform and landing (Hinrichs et al, 1985;Larkin and Parker, 1998;McMillan et al, 2010;Kim and Lim, 2014;Christoforidou et al, 2017;Estevan et al, 2020;Schroeder et al, 2021;Koo et al, 2022;Moir et al, 2022), and (2) jump-land tasks, which entails jumping horizontally or upwards (off a box or not) and landing (Hass et al, 2003;Russell et al, 2007;Xu et al, 2020). Despite of the possible differences related to the task specificity, previous literature presented evidence that pre-pubescent children between 7 and 12 years are less efficient diminishing the rate loading (higher peak of forces and shorter time to these peaks and also to the end of the braking phase) (Larkin and Parker, 1998;McKay et al, 2005;Lazaridis et al, 2010) because of: (1) their anticipatory strategies rely mostly on their muscle activation with higher time of activation before impact (Christoforidou et al, 2017); (2) during the impact they increase the muscle co-activity of the knee muscles but not the ones related to the ankle dorsiflexion (Croce et al, 2004;Russell et al, 2007;Wild et al, 2009), and (3) after impact, they tend to present more proximal-distal control with more muscle co-activity and limited range of motion of the lower limb joints in the sagittal plane (Hinrichs et al, 1985;Larkin and Parker, 1998;Hass et al, 2003;Croce et al, 2004;Kim and Lim, 2014;DiStefano et al, 2015;Raffalt et al, 2017;Niespodziński et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the literature highlights how landing technique is sport-specific in young athletes and how this varies in relation to the sport played especially in prepubertal age (Estevan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the recruitment of participants, it was limited to sport science students and not to experienced jumpers because the former may increase the generalizability of the results considering that drop jump exercises are not only performed to improve the reactive strength of athletes but also to prevent interventions [ 24 , 56 , 57 ]. This is the reason why our study should be generalized with caution to athletes.…”
Section: Discussionmentioning
confidence: 99%